Category Of Complement And Semantic Role Of Single Argument In Balinese Syntactic Constructions - I Nyoman Kardana; I Made Beni Wrihatnala; Made Sri Satyawati (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2016)
This study aims to analyze and describe the word category of complement and semantic roles of single argument found in syntactic constructions with complement in Balinese language. Data of this study was collected from Balinese speaking informants living in the city of Denpasar, Bali. The data was supported by those obtained from Balinese story books. The data was collected by observation method completed with recording and note taking techniques. The collected data was analyzed based on theory of semantic role proposed by Van Valin and LaPolla, 1997 and by I Saeed, 1997. The result shows that complement in Balinese can be filled in by noun, adjective, numeral, and verb. The verb predicate of constructions with complement are mostly intransitive verb with ma- but in few data of intransitive verb with N- are also found. Then, the semantic roles of single argument in constructions with complement are agent, experiencer, patient, and recipient.Â Key words: complement, semantic role, argument, intransitive, transitive.